Temporally Variable Geographical Distance Effects Contribute to the Assembly of Root-Associated Fungal Communities - Barnes, Christopher J.; van der Gast, Christopher J.; Burns, Caitlin A.; McNamara, Niall P.; Bending, Gary D. (Frontiers in Microbiology, 2016)
Root-associated fungi are key contributors to ecosystem functioning, however the factors which determine community assembly are still relatively poorly understood. This study simultaneously quantified the roles of geographical distance, environmental heterogeneity and time in determining root-associated fungal community composition at the local scale within a short rotation coppice (SRC) willow plantation. Culture independent molecular analyses of the root-associated fungal community suggested a strong but temporally variable effect of geographical distance between fungal communities on composition at the local geographical level. Whilst these distance effects were most prevalent on October communities, soil pH had an effect on structuring of the communities throughout the sampling period. Given the temporal variation in the effects of geographical distance and the environment for shaping root-associated fungal communities, there is clearly need for a temporal component to sampling strategies in future investigations of fungal biogeography.